PERAN IDI DALAM PENGEMBANGAN ILMU PENGETAHUAN KEDOKTERAN DI INDONESIA - Sahrin, Alpi; Kusuma, A M Naitul Jaya; Yusuf, Hudi (Cahaya Ilmu Bangsa, 2025)
This journal delves into the significant role played by the Indonesian Medical Association (IDI) in the development of medical science in Indonesia. As a leading medical professional organization in Indonesia, IDI has played a crucial role in improving medical practice standards, advocating for public health, and advancing medical research in the country. Through a comprehensive review of IDI's history, programs, and contributions, this journal aims to present a detailed overview of the concrete efforts undertaken by IDI in advancing the field of medical science in Indonesia. Using a descriptive analysis approach, this journal gathers relevant data and information to meticulously describe IDI's role in shaping and developing medical science in Indonesia. Therefore, the analytical findings of this journal will provide broad and in-depth insights for all stakeholders in the healthcare sector to better understand and appreciate the contributions and positive impact made by IDI in strengthening the national healthcare system and enhancing the quality of medical services in the country. It is hoped that this journal can serve as an important reference for academics, healthcare practitioners, policymakers, and other relevant parties in strengthening cooperation and collaboration to continue driving the advancement of medical science in Indonesia for the well-being and safety of all members of society. Jurnal ini membahas secara mendalam peran penting yang dimainkan oleh Ikatan Dokter Indonesia (IDI) dalam pengembangan ilmu pengetahuan kedokteran di Indonesia. IDI, sebagai organisasi profesi medis terkemuka di Indonesia, telah berperan secara signifikan dalam meningkatkan standar praktik medis, memperjuangkan kesehatan masyarakat, serta memajukan penelitian medis di negara ini. Melalui tinjauan yang komprehensif terhadap sejarah, program, dan kontribusi IDI, jurnal ini bertujuan menyajikan gambaran detil tentang upaya-upaya konkret yang telah dilakukan oleh IDI dalam memajukan bidang ilmu kedokteran di Indonesia. Dengan menggunakan pendekatan analisis deskriptif, jurnal ini mengumpulkan data dan informasi terkini yang relevan untuk menggambarkan secara seksama peran IDI dalam membentuk dan mengembangkan ilmu kedokteran di Indonesia. Oleh karena itu, hasil analisis dari jurnal ini akan memberikan wawasan yang luas dan mendalam bagi seluruh pemangku kepentingan di bidang kesehatan untuk lebih memahami serta mengapresiasi kontribusi serta dampak positif yang telah dilakukan oleh IDI dalam memperkuat sistem kesehatan nasional dan meningkatkan kualitas pelayanan medis di tanah air. Diharapkan bahwa jurnal ini dapat menjadi sumber rujukan yang penting bagi para akademisi, praktisi kesehatan, pengambil kebijakan, serta pihak-pihak terkait lainnya dalam memperkuat kerja sama dan kolaborasi guna terus mendorong kemajuan ilmu kedokteran di Indonesia demi kesejahteraan dan keselamatan hidup seluruh masyarakat.